2020
DOI: 10.1111/bjh.16519
|View full text |Cite
|
Sign up to set email alerts
|

Association between hydroxycarbamide exposure and neurocognitive function in adolescents with sickle cell disease

Abstract: Summary Patients with sickle cell disease (SCD) are at increased risk for neurocognitive impairments. While disease‐modifying treatment, such as hydroxycarbamide (hydroxyurea), may decrease this risk, it has not been systematically investigated in children with SCD. We screened neurocognitive functioning in 103 adolescents with SCD (16–17 years, 50% female) and compared outcomes between patients with a history of exposure to hydroxycarbamide (n = 12 HbSC/HbSβ+ thalassaemia; n = 52 HbSS/HbSβ0 thalassaemia) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 57 publications
2
29
2
Order By: Relevance
“…Recurrent micro‐infarctions and chronic hypoxic damage likely contribute to the development of cognitive deficits 42 . Our group and others have shown that treatment with hydroxycarbamide and elevated fetal haemoglobin were linked to improved cognitive functioning 23,43,44 . Although we did not establish a relationship between favourable transition outcomes and disease‐modifying therapy in our analysis, hydroxycarbamide may mitigate cognitive deficit in adolescents with SCD.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Recurrent micro‐infarctions and chronic hypoxic damage likely contribute to the development of cognitive deficits 42 . Our group and others have shown that treatment with hydroxycarbamide and elevated fetal haemoglobin were linked to improved cognitive functioning 23,43,44 . Although we did not establish a relationship between favourable transition outcomes and disease‐modifying therapy in our analysis, hydroxycarbamide may mitigate cognitive deficit in adolescents with SCD.…”
Section: Discussionmentioning
confidence: 58%
“…SCCRIP participants receive neurocognitive screening every four years starting at age four 20,23 . As these assessments were not clinical referrals, participants were not selected for prior neurologic findings, disease severity, or concern for cognitive decline.…”
Section: Methodsmentioning
confidence: 99%
“…In another report, older age and low hemoglobin were associated with increased neurocognitive impairment 33 . HbF has been associated with significantly better verbal fluency in a study of adolescents 9 and better scores on particular cognitive measures in a study of adults 34 …”
Section: Discussionmentioning
confidence: 94%
“…Without chronic transfusion, these patients' risk of recurrent stroke is .50%. 1 Although treatment with hydroxyurea also provides some cerebrovascular benefits for patients with SCA, [2][3][4][5][6][7][8][9][10] chronic transfusion offers better stroke protection. Based on the results of the Stroke With Transfusions Changing to Hydroxyurea (SWiTCH) clinical trial, patients with a history of stroke ideally should not transition to hydroxyurea-only treatment, because this may increase their risk of stroke.…”
mentioning
confidence: 99%